Systematic Literature Review: Audit Committee on Audit Report Lag - Jenny Liana; Enggar Diah Puspa Arum; Wiralestari (Cita konsultindo, 2026)
This study aims to review articles related to the effect of the audit committee on audit report lag. A bibliometric-based Systematic Literature Review (SLR) method is employed to identify, evaluate, and synthesize relevant empirical findings from the reputable Scopus database. The literature search was conducted using a combination of the keywords “audit committee” and “audit report lag.” Of the 64 articles initially identified, 20 articles met the inclusion criteria after a screening process using the PRISMA protocol. The findings indicate that audit report lag is an important indicator of reporting quality, influenced by a combination of firm-level internal factors, auditor characteristics, and governance mechanisms. Several studies position the audit committee as a governance mechanism that affects not only the quality of financial reporting but also the speed with which reports reach the market. The impact of the audit committee on audit report lag is not one-directional: a committee that is “strong but overly busy” may prolong the process, whereas a committee that is independent, expert, focused, and led by a competent chairperson can act as a key catalyst in improving the timeliness of financial reporting.